Desain Mesin Pencacah Botol Plastik Menggunakan Tenaga Surya - Yahya, Muhtar, Hasyim Asy'ari, ST., MT (2017)
Garbage is unwanted residual material after the end of a process that tends to destroy society. Trash is one of the many social problems faced by the community. As for the types of waste that is both organic and inorganic, organic waste can usually be explained through natural processes, in contrast to inorganic waste countless long time decoder, such as plastic bottles litter example. To solve the problem of waste, required a technology to process waste itself. Several studies have been done, such as the manufacture of plastic bottles thrasher using electrical energy. This technology requires operating costs for electrical energy alone. For this study aims to design thrasher plastic bottles using solar power. Sunlight energy is converted or converted by the solar panels into electrical energy, electrical energy is used to supply a DC motor. The method of this research is to design thrasher plastic bottles using solar power with 15 rotating blades and 2 remain attached to the cover. Then use a 24-volt DC motor 19 amperes, two solar panels that capacity 100Wp respectively, then the use of the gear box using a chain so that it is big enough Rpm. The results of this study, the machine can work counts 1 bottles with less than 5 minutes. Hourly machine is capable of chopping of approximately 14 plastic bottles and plastic produced ore size of about 1 to 2 cm. Thrasher plastic bottles can work from 10:00 to 14:00 and at 11:00 until 13:00 the machine can work optimally. Because the size of this machine is not a measure for the industry so many shortcomings in the operation of chopping and plastic bottles are inserted gradually. The ability of a thrasher depends by the intensity of sunlight, smoke, dust, moisture and wind speed. Obtaining the results at the time of low light intensity obtained voltage of 9.7 volts and a current of 5.46 amperes and the machine can work, in conditions of high light intensity gain of 19.1 volts and a current of 6.23 amperes and the machine can work optimally. In working machine can be chopped 1 bottle of 600 ml volume with less than 4.5 minutes / bottle at 11:00. Thrasher necessary application on a large scale in order to work properly and effectively.